Adsorption of Maxilon Blue GRL from an Aqueous Solution: Equilibrium and Kinetic Studies - Koyuncu, Menderes (Asian Journal of Chemistry, 2010)
Removal of a basic dye, maxilon blue GRL by bentonite, from an aqueous solution was studied. The adsorption of the dye on to bentonite was investigated during batch adsorption experiments carried out to determine the effect of initial dye concentration and contact time. The Langmuir and Freundlich isotherm models were tested for their applicability. Kinetic studies were conducted in two different temperatures and five different reaction periods. Adsorption stability studies were done with five different dye solutions at 37 ºC, pH 4.5-5.0 and in 10 h stability periods and adsorption capacities, adsorption stability constants and Langmuir and Freundlich constants were calculated. The experimental data were analysed using the pseudo-first-order adsorption kinetic model. According to this model, the rate constants were evaluated for two different temperatures. The experimental data fit the first-order kinetic model.